2021
DOI: 10.1101/2021.11.16.468815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutant KRAS modulates colorectal cancer cells invasive response to fibroblast-secreted factors through the HGF/C-MET axis

Abstract: Genetic alterations influence the malignant potential of cancer cells, and so does the tumor microenvironment. Herein, we combined the study of KRAS oncogenic effects in colorectal cancer cells with the influence of fibroblasts-derived factors. Results revealed that mutant KRAS regulates cell fate through both autonomous and non-autonomous signaling mechanisms. Specifically, processes such as proliferation and cell-cell aggregation were autonomously controlled by mutant KRAS independently of the stimulation wi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…HGF was not detected in the CM from CRC cells alone. In accordance with our previous results 22 , non-activated and rhTGFβ1-activated fibroblasts produce similar levels of HGF. Though, challenging of fibroblasts with CM resulted in a significant increase in HGF production in all conditions (Figure 1D).…”
Section: Crc Cells Secreted Factors Influence the Expression Of α-Sma...supporting
confidence: 93%
See 2 more Smart Citations
“…HGF was not detected in the CM from CRC cells alone. In accordance with our previous results 22 , non-activated and rhTGFβ1-activated fibroblasts produce similar levels of HGF. Though, challenging of fibroblasts with CM resulted in a significant increase in HGF production in all conditions (Figure 1D).…”
Section: Crc Cells Secreted Factors Influence the Expression Of α-Sma...supporting
confidence: 93%
“…Previous work from our group 22 and others 23 demonstrated that HGF is an important fibroblast-secreted pro-invasive factor. Also, HGF has been reported to induce the activation of fibroblasts, supporting their tumor promoting characteristics 24 .…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, more integrative studies are needed to better understand the impact of the microenvironment on KRAS-driven signaling and therapy response/resistance. In line with this, our group has recently shown that mutKRAS can regulate functional effects autonomously or it can cooperate with fibroblast-secreted factors to modulate cancer cell invasive behavior [19].…”
Section: Introductionmentioning
confidence: 75%
“…These apparent dichotomic responses go in line with our results demonstrating opposite invasive responses to fibroblast-secreted factors. While in HCT116, KRAS inhibition impaired invasion induced by fibroblasts-derived HGF, in LS174T KRAS inhibition triggered invasion [19]. Moreover, both cell lines commonly upregulated proteins associated with exosomes localization upon KRAS silencing and culture with FibCM.…”
Section: Discussionmentioning
confidence: 91%